The Role of the Hippo Pathway in Melanocytes and Melanoma - Baguley, Bruce C.; Finlay, Graeme J.; Kim, Ji Eun (Frontiers in Oncology, 2013)
The Hippo signalling pathway comprises a series of cytoplasmic tumour suppressor proteins including Merlin and the Lats1/2 and MST1/2 kinases, and is thought to play a critical role in determining the sizes of organs and tissues. The Hippo pathway is regulated upstream by extracellular mechanosensory signalling arising from cell shape and polarity, as well as by a variety of extracellular signalling molecules. When active, the pathway maintains the transcriptional activators YAP and TAZ in phosphorylated forms in the cytoplasm, preventing cell proliferation. When the Hippo pathway is inactivated, YAP and TAZ are translocated to the nucleus and induce the expression of a variety of proteins concerned with entry into the cell division cycle, such as cyclin D1 and Fox M1, as well as the inhibition of apoptosis. The failure of the Hippo pathway has been implicated in the development of many different types of cancer but there is limited information available as to its involvement in melanoma. We hypothesise here firstly that the Hippo pathway is involved in maintaining density of cutaneous melanocytes on the basement membrane at the junction of the epidermis and the dermis, and secondly, that its function is disturbed in melanoma. We have analysed a series of 23 low passage human melanoma lines as well as in cultures of normal melanocytes, and find that melanocytes, as well as all melanoma cell lines examined express TAZ. Melanocytes and most melanoma lines also express YAP. E-cadherin, an upstream regulator of the Hippo pathway, and Axl, a receptor tyrosine kinase regulated by the Hippo pathway, are expressed in melanocytes and in several melanoma cell lines. These observations, together with published evidence for the presence of Merlin, Lats1/2 and MST1/2 in melanocytes and melanoma cells, support the hypothesis that the Hippo pathway is an important component of melanocyte and melanoma behaviour.